The Effect of Halal Labeling and Religiosity on Buyers Decisions on Halal Cosmetic Products (Case Study of Umsu Students) - Rini Wardani; Novien Rialdy (Penerbit Merdeka Kreasi, 2023)
This study aims to analyze the effect of halal labeling and religiosity on buyers' decisions of halal cosmetic products, this research uses quantitative research techniques, involving field research, this research was conducted at Muhammadiyah University of North Sumatra, In this study, there is an effect of halal labeling on purchasing decisions because the value of t count > t table (5.895> 2.010) and a significance level of 0.000 <0.05. In this study, there is an influence of religiosity on purchasing decisions because the value of t count > t table (4.157> 2.010) and a significance level of 0.000 <0.05. In this research, it can be seen that the f table value is 146,593 and the significance level is 0,000. In this study, both Religiosity and Halal Labeling have an influence on purchasing decisions because f count > f table (146,593 > 2.80) and significance level (0,000 <0.05), the value of R Square is 0.859 or 85.9% contribution of independent variables (Religiosity and Halal Labeling) to Purchase Decision while the remaining 14.1% is influenced by other factors not examined in this study.